Dissolved organic carbon, salinity, electrical conductivity, suspended particulate matter, and isotopic composition of sea ice cores sampled in the coastal zone of the southern Canadian Beaufort Sea, near Herschel Island - Qikiqtaruk - Michael Fritz; Kristoffer Laux; Bennet Juhls (PANGAEA, 2025)
Isotope analyses at AWI Potsdam were performed using DELTA-S Finnigan MAT mass spectrometers (USA) employing the equilibration method, described in Meyer et al. (2000). The isotope ratios are reported in per mil ( extperthousand) relative to the Vienna Standard Mean Ocean Water (VSMOW) as the international reference standard. In addition to the δ^1?O and δD values, the second-order parameter deuterium excess (d) was calculated according to the equation (after Dansgaard, 1964): d = δD - 8 exttimes δ^1?O
In: Fritz, M et al. (2025): Organic and inorganic geochemical properties of sea ice cores in the nearshore zone of the southern Canadian Beaufort Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984649